Design and engineering of organic molecules for customizable terahertz tags - Ray, Shaumik; Dash, Jyotirmayee; Nallappan, Kathirvel; Kaware, Vaibhav; Basutkar, Nitin; Ambade, Ashootosh; Joshi, Kavita; Pesala, Bala (Terahertz, RF, Millimeter, and Submillimeter-Wave Technology and Applications VII, 2014)
Terahertz (THz) frequency band lies between the microwave and infrared region of the electromagnetic spectrum. Molecules having strong resonances in this frequency range are ideal for realizing "Terahertz tags" which can be easily incorporated into various materials. THz spectroscopy of molecules, especially at frequencies below 10 THz, provides valuable information on the low frequency vibrational modes, viz. intermolecular vibrational modes, hydrogen bond stretching, torsional vibrations in several chemical and biological compounds. So far there have been very few attempts to engineer molecules which can demonstrate customizable resonances in the THz frequency region. In this paper, Diamidopyridine (DAP) based molecules are used as a model system to demonstrate engineering of THz resonances (< 10 THz) by fine-tuning the molecular mass and bond strengths. Density Functional Theory (DFT) simulations have been carried out to explain the origin of THz resonances and factors contributing to the shift in resonances due to the addition of various functional groups. The design approach presented here can be easily extended to engineer various organic molecules suitable for THz tags application.

Terahertz spectroscopy and solid-state density functional theory calculations of cyanobenzaldehyde isomers - Dash, Jyotirmayee; Ray, Shaurnik; Nallappan, Kathirvel; Kaware, Vaibhav; Basutkar, Nitin B.; Gonnade, Rajesh G.; Ambade, Ashootosh V.; Joshi, Kavita; Pesala, Bala (Journal of Physical Chemistry A, 2015)
Spectral signatures in the terahertz (THz) frequency region are mainly due to bulk vibrations of the molecules. These resonances are highly sensitive to the relative position of atoms in a molecule as well as the crystal packing arrangement. To understand the variation of THz resonances, THz spectra (2-10 THz) of three structural isomers: 2-, 3-, and 4-cyanobenzaldehyde have been studied. THz spectra obtained from Fourier transform infrared (FTIR) spectrometry of these isomers show that the resonances are distinctly different especially below 5 THz. For understanding the intermolecular interactions due to hydrogen bonds, four molecule cluster simulations of each of the isomers have been carried out using the B3LYP density functional with the 6-31G(d,p) basis set in Gaussian09 software and the compliance constants are obtained. However, to understand the exact reason behind the observed resonances, simulation of each isomer considering the full crystal structure is essential. The crystal structure of each isomer has been determined using X-ray diffraction (XRD) analysis for carrying out crystal structure simulations. Density functional theory (DFT) simulations using CRYSTAL14 software, utilizing the hybrid density functional B3LYP, have been carried out to understand the vibrational modes. The bond lengths and bond angles from the optimized structures are compared with the XRD results in terms of root-mean-square-deviation (RMSD) values. Very low RMSD values confirm the overall accuracy of the results. The simulations are able to predict most of the spectral features exhibited by the isomers. The results show that low frequency modes (<3 THz) are mediated through hydrogen bonds and are dominated by intermolecular vibrations.

Tuning of terahertz resonances of pyridyl benzamide derivatives by electronegative atom substitution - Dash, Jyotirmayee (Journal of Infrared, Millimeter, and Terahertz Waves, 2018)
N-(pyridin-2-yl) benzamide (Ph2AP)-based organic molecules with prominent terahertz (THz) signatures (less than 5 THz) have been synthesized. The THz resonances are tuned by substituting the most electronegative atom, fluorine, at ortho (2F-Ph2AP), meta (3F-Ph2AP), and para (4F-Ph2AP) positions in a Ph2AP molecule. Substitution of fluorine helps in varying the charge distribution of the atoms forming hydrogen bond and hence strength of the hydrogen bond is varied which helps in tuning the THz resonances. The tuning of lower THz resonances of 2F-Ph2AP, 3F-Ph2AP, and 4F-Ph2AP has been explained in terms of compliance constant (relaxed force constant). Four-molecule cluster simulations have been carried out using Gaussian09 software to calculate the compliance constant of the hydrogen bonds. Crystal structure simulations of the above molecules using CRYSTAL14 software have been carried out to understand the origin of THz resonances. It has been observed that THz resonances are shifted to higher frequencies with stronger hydrogen bonds. The study shows that 3F-Ph2AP and 4F-Ph2AP have higher hydrogen bond strength and hence the THz resonances originating due to stretching of intermolecular hydrogen bonds have been shifted to higher frequencies compared to 2F-Ph2AP. The methodology presented here will help in designing novel organic molecules by substituting various electronegative atoms in order to achieve prominent THz resonances.
Keywords: Compliance constant; Density functional theory; Ph2AP molecule; Terahertz spectroscopy

Fine-tuning of Terahertz resonances in hydrogen-bonded organic molecular complexes - Dash, Jyotirmayee; Ray, Shaumik; Devi, Nirmala; Basutkar, Nitin; Ambade, Ashootosh V.; Pesala, Bala (Journal of Molecular Structure, 2019)
Novel organic molecular complexes have been designed and synthesized to obtain prominent Terahertz (THz) resonances in the low-frequency region. Intermolecular hydrogen bonds give rise to low-frequency THz resonances and hence binary organic molecular complexes of pyridyl alkylamide/benzamide (DAP) and hexyl thymine (C6THY) with multiple strong intermolecular hydrogen bonds (N-H–-O and N-H–-N) are designed and synthesized. THz resonances of the complexes are fine-tuned by varying the number of benzene rings in the DAP moiety (PrDAP + C6THY, PrPhDAP + C6THY and PhDAP + C6THY). DFT simulation studies of two molecule clusters have been carried out to understand the origin of low-frequency THz resonances. It has been observed that the lowest THz resonances (< 2 THz) originate due to translation/rotation of the whole crystal structure and the resonances from 2 to 4 THz are mainly due to intermolecular hydrogen bond bending/stretching vibrations. In order to understand the individual hydrogen bond strengths, compliance constants, which are inverse of the force constants are calculated and Natural Bond Orbital (NBO) analysis has been carried out. Comparison of the experimental THz spectra of different complexes shows that there is a small but tunable variation in THz resonances from one complex to another. Tuning of THz resonances has potential applications in designing THz tags, which can be used in various anti-counterfeiting applications such as currency notes, pharmaceutical tablets. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Compliance constant; Natural bond orbital analysis; Organic molecular complex; Terahertz spectroscopy